The effect of oblique blast loadings on moment and braced frames in steel structures. Issue 4 (April 2016) - Shiravand, MR; Shabani, MJ
Due to the increasing use of vehicle bombs on attacking important buildings by terrorist organizations around the world, it is necessary to design buildings with more resistance against blast loads. In this research, numerical studies have been done for three-dimensional structural models of special moment frames, concentrically braced frames, and eccentrically braced frames with 3, 5, and 10 stories. The nonlinear dynamic method is applied for analyzing the models under two different levels of straight and oblique blast loadings based on the UFC 3-340-02. The plastic hinge rotations, ductility ratios, performance levels, and flexural moments in the models are obtained from the analysis and compared with each other. According to the results, it can be said that the eccentrically braced frame systems generally show better performances than other systems under blast loadings. Also due to different shock directions, the values of column plastic rotations and bending moments under oblique blast loadings are less than straight ones.